2014
DOI: 10.1128/aem.01357-14
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metformin on Metabolic Improvement and Gut Microbiota

Abstract: bMetformin is commonly used as the first line of medication for the treatment of metabolic syndromes, such as obesity and type 2 diabetes (T2D). Recently, metformin-induced changes in the gut microbiota have been reported; however, the relationship between metformin treatment and the gut microbiota remains unclear. In this study, the composition of the gut microbiota was investigated using a mouse model of high-fat-diet (HFD)-induced obesity with and without metformin treatment. As expected, metformin treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
277
5
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(320 citation statements)
references
References 33 publications
26
277
5
12
Order By: Relevance
“…In addition, metformin increases blood levels of GLP-1, an insulin sensitizing hormone, by promoting its secretion through a gut bacteria-related mechanism [15] . Metformin has also been shown to upregulate certain probiotics, such as A muciniphila and lactobacillus, and importantly, this modulation was associated with the beneficial effects of metformin on gut barrier function and glucose metabolism [14,16] . Because metformin modulates the composition of gut bacteria and enhances gut barrier function, we inferred that the alteration of the gut bacteria community by metformin may reduce LPS absorption by reducing its absorption via protecting gut integrity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, metformin increases blood levels of GLP-1, an insulin sensitizing hormone, by promoting its secretion through a gut bacteria-related mechanism [15] . Metformin has also been shown to upregulate certain probiotics, such as A muciniphila and lactobacillus, and importantly, this modulation was associated with the beneficial effects of metformin on gut barrier function and glucose metabolism [14,16] . Because metformin modulates the composition of gut bacteria and enhances gut barrier function, we inferred that the alteration of the gut bacteria community by metformin may reduce LPS absorption by reducing its absorption via protecting gut integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent studies indicate that the modulatory effect of metformin on the gut microbiota is related to its anti-inflammatory and anti-obesity as well as its therapeutic efficacy on glucose metabolism [14][15][16] . For example, feeding a HFD to mice leads to a reduction in the probiotic Akkermansia muciniphila (A muciniphila) in the gut, which is important in maintaining the integrity of the gut barrier and insulin sensitivity [16] , while metformin has recently been shown to reverse this reduction [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few months later, Lee et al confirmed that metformin treatment induces an increase in the A. muciniphila population and demonstrated a negative correlation between glycaemia and A. muciniphila abundance. Interestingly, co-incubation of metformin and mouse stool samples led to an enrichment in A. muciniphila [51], suggesting that metformin directly interacts with the gut microbiota to foster the growth of A. muciniphila.…”
Section: Dysbiosis Related To Type 2 Diabetes and Hyperglycaemiamentioning
confidence: 99%
“…62 Metformin increases the abundance of Akkermansia, a mucus-degrading gram-negative bacteria in the gut, which is associated with restoration of reduced regulatory T cells and amelioration of low-grade tissue inflammation in the adipose tissue of obese animals. 63 This effect of metformin on intestines probably causes anti-aging and anti-cancerous effects and life span extension, the effects which need verification.…”
mentioning
confidence: 99%